Generation of biofuels from rice straw and its future perspectives - Biswas, P.; Mandal, S.; Das, T.; Dey, S.; Ghorai, M.; Bhattacharya, S.; Ghosh, A. (Elsevier, 2023)
Proper management of waste requires a huge investment and proper recycling of this waste can be a source of wealth to the society. Huge amounts of biodegradable wastes are produced by agricultural sector which comprises mainly of the nonedible portion which can be successfully converted to value-added biological products and biofuels. This biofuel can serve as an inexpensive alternative of fossil fuels and is considered as an eco-friendly and cost-effective option. The mechanization, along with swift alterations from political, social, and economic aspects have resulted in accelerating the process of harvesting during rice cultivation which have resulted in the increase of open-field burning of straw. The open-field burning of straw results in subsequent nutrient loss, air pollution, more emissions of greenhouse gasses, and health disorders. Generation of biofuels from these rice straws and its applications can not only reduce dependence on fossil fuels but also reduces greenhouse gas (GHGs) emissions, and boosts the concept of sustainable development. This chapter mainly deals with recent research reports and documentation associated with production of biofuel from rice straw. The chapter also discusses the future perspectives of biofuel production from rice straw which may reduce numerous environmental issues and health hazards generated by open field burning of rice stubbles. © 2023 Elsevier Inc. All rights reserved.
Keywords: Agricultural Residue; Biofuels; Greenhouse Gas; Rice Straw